2006
DOI: 10.1158/1078-0432.ccr-05-1913
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Leptin and the Leptin Receptor as a Marker of Breast Cancer Progression: Possible Role of Obesity-Related Stimuli

Abstract: Purpose: Recent in vitro studies suggested that the autocrine leptin loop might contribute to breast cancer development by enhancing cell growth and survival. To evaluate whether the leptin system could become a target in breast cancer therapy, we examined the expression of leptin and its receptor (ObR) in primary and metastatic breast cancer and noncancer mammary epithelium. We also studied whether the expression of leptin/ObR in breast cancer can be induced by obesityrelated stimuli, such as elevated levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
293
4
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 322 publications
(334 citation statements)
references
References 41 publications
27
293
4
5
Order By: Relevance
“…However, the interplay between Acrp30 and other growth factors has been shown to be important for Acrp30's ability to inhibit cell proliferation (Wang et al, 2005). With respect to breast cancer, and obesity, leptin has been an adipokine implicated in mammary tumorigenesis (Hu et al, 2002;Cleary et al, 2003;Frankenberry et al, 2006;Garofalo et al, 2006). Overweight or obese individuals usually have elevated levels of the growth factor leptin, which is positively correlated to body mass index while Acrp30 is negatively correlated with body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interplay between Acrp30 and other growth factors has been shown to be important for Acrp30's ability to inhibit cell proliferation (Wang et al, 2005). With respect to breast cancer, and obesity, leptin has been an adipokine implicated in mammary tumorigenesis (Hu et al, 2002;Cleary et al, 2003;Frankenberry et al, 2006;Garofalo et al, 2006). Overweight or obese individuals usually have elevated levels of the growth factor leptin, which is positively correlated to body mass index while Acrp30 is negatively correlated with body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…9 Tissue samples were obtained from women who underwent partial or total mastectomy for primary breast cancer. The age of patients ranged from 45 to 71 years.…”
Section: Breast Cancer Patients and Samplesmentioning
confidence: 99%
“…[6][7][8] Interestingly, overexpression of the leptin system in breast cancer appears to be associated with higher tumor grade and size. [9][10][11][12][13] The mechanisms of leptin overexpression in breast cancer cells is partially known, for instance, we have shown that leptin transcription and synthesis can be induced by hypoxia or high levels of insulin. 9,13,14 Here we investigated whether leptin expression in breast cancer cells could be related to the existence of the Lep-2548G/A polymorphism in the promoter region of leptin gene.…”
mentioning
confidence: 99%
“…Both leptin and ObR expressions are more abundant in tumours with a high grade [57]. Interestingly, leptin and ObR are co-expressed in primary breast carcinoma, suggesting that leptin acts on mammary tumour cells via an autocrine pathway [55].…”
Section: Leptin and Breast Cancermentioning
confidence: 99%